Phylogenomic reappraisal of the Neotropical catfish family Loricariidae (Teleostei: Siluriformes) using ultraconserved elements - Roxo, Fábio F. [UNESP] (2019)
Neotropical freshwaters host more than 6000 fish species, of which 983 are suckermouth armored catfishes of the family Loricariidae – the most-diverse catfish family and fifth most species-rich vertebrate family on Earth. Given their diversity and ubiquitous distribution across many habitat types, loricariids are an excellent system in which to investigate factors that create and maintain Neotropical fish diversity, yet robust phylogenies needed to support such ecological and evolutionary studies are lacking. We sought to buttress the systematic understanding of loricariid catfishes by generating a genome-scale data set (1041 loci, 328,330 bp) for 140 species spanning 75 genera and five of six previously proposed subfamilies. Both maximum likelihood and Bayesian analyses strongly supported the monophyly of Loricariidae. Our results also reinforced the established backbone of loricariid interrelationships: Delturinae as sister to all other analyzed loricariids, with subfamily Rhinelepinae diverging next, followed by Loricariinae sister to Hypostominae + Hypoptopomatinae. Previous DNA-based relationships within Hypostominae and Loricariinae were strongly supported. However, we evaluated for the first time DNA-based relationships among many Hypoptopomatinae genera and found significant differences with this subfamily's current genus-level classification, prompting several taxonomic changes. Finally, we placed our topological results within a fossil-calibrated temporal context indicating that early Loricariidae diversification occurred across the Cretaceous-Paleogene boundary ∼65 million years ago (Ma). Our study lays a strong foundation for future research to focus on relationships among species and the macroevolutionary processes affecting loricariid diversification rates and patterns.